Transport driven by eddy momentum fluxes in the Gulf Stream Extension region - Greatbatch, R; Zhai, X; Claus, M; Czeschel, L; Rath, W (2010)
The importance of the Gulf Stream Extension region in climate and seasonal prediction research is being increasingly recognised. Here we use satellite-derived eddy momentum fluxes to drive a shallow water model for the North Atlantic Ocean that includes the realistic ocean bottom topography. The results show that the eddy momentum fluxes can drive significant transport, sufficient to explain the observed increase in transport of the Gulf Stream following its separation from the coast at Cape Hatteras, as well as the observed recirculation gyres. The model also captures recirculating gyres seen in the mean sea surface height field within the North Atlantic Current system east of the Grand Banks of Newfoundland, including a representation of the Mann Eddy. © 2010 by the American Geophysical Union.